BENEFITS OF USING CYBER FICTION FOR STUDENT READING SKILLS - Barokah Ilahi; Mutiarani Mutiarani (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Language is the medium people use to express their thoughts and needs to others. In addition to their native or national language, some people use English as a second language in certain situations. Education is not far from reading. Reading is very important for obtaining knowledge and information from various sources such as books and the Internet. Language, education will always be related to the internet. Technological advances that have given rise to many social media, online games, etc. require teachers to keep up with these advances and make the most of this technology in the world of education. Especially in Indonesia, many young people are not very interested in reading. In this study, researchers used quantitative studies. A preliminary experimental study was conducted to prove that teachers can use cyber-fiction to improve or influence student’s reading comprehension. In this study, researchers will conduct a pre-test, an experiment, and a post-test. The Calculations use the SPSS for Windows t-test. The effect of cyber fiction on improving students' reading comprehension was tested using a t-test, with the aim of separately testing for significant effects of the dependent variable on the independent variable. Results of a Test Using SPSS to Predict Student Reading Improvements Through the Use of Cyber Fiction. It can be concluded that cyber fiction conducted in Class XI IPA 4 of SMAN 1 PATOKBEUSI has a positive and significant impact on student’s reading comprehension.